Sustainability elements of companies that are affected by pandemics - Anneke M. Moolman; Jaco P. Fouché; Verona Leendertz (Journal of Economic and Financial Sciences, 2023)
Orientation: The havoc created by COVID-19 reaffirmed the pervasive effects of pandemics on companies’ sustainability, which has become an increasingly important consideration for stakeholders.